The Peruvian Society of Obstetrics and Gynecology and public health - Guzmán Changanaquí, Alfredo (2017)
During its 70 years of institutional life, the Peruvian Society of Obstetrics and Gynecology has contributed not only to the development of the specialty, but also of the country’s Public Health, through its Congresses, Symposia, round tables, courses, and The Peruvian Journal of Gynecology and Obstetrics. There were 48 articles related with public health aspects published in the institutional journal only. However, certain topics have been more exposed than others due to their relevance. We will review them in this article.